Are Two Parents Better than One? Examining the Effects of Biparental Care on Parental and Egg Clutch Mass in the Stomatopod Pullosquilla Thomassini (). Issue 1 (1st January 2015) - Wright, Mary L.; Caldwell, Roy L.
Abstract: Among marine crustaceans, biparental care has only been directly observed in the stomatopod genus Pullosquilla . This study investigated the evolutionary maintenance of biparental care in Pullosquilla thomassini (Manning, 1978 ) by examining fitness costs and benefits of biparental care using a manipulation of the number and sex of care providers. In the absence of parental care, egg clutch mass decreased. However, in the presence of at least one parent, there were no changes in clutch mass during the experiment. This suggests that while parental care increases production of offspring, uniparental care by either sex is sufficient. We suggest that biparental care may increase fitness in P. thomassini by facilitating the production of overlapping egg clutches. We found evidence that males providing uniparental care lost body mass, suggesting they pay a small cost in fitness. However, single males with eggs were rare at our field site (3.93% of burrows).